How economic ideas evolve the impact of religion on the German and Italian welfare state - Hien, Josef 1981- (Cambridge, United Kingdom Cambridge University Press, 2025)
"This book demonstrates the link between religious ideas and the diverging development of economies and welfare states in Europe. The work provides an analysis of the contextual factors that steered religious development and expands historical sociology by focusing on religious ideas and their long term developmental trajectories in politics." - Provided by publisher
Josef Hien, IFFS 30.10.2024 -- Catholicism and the formation of the German welfare state -- Catholicism and the Italian Welfare State in the 19th century -- Protestantism and Catholicism in German postwar reconstruction -- The influence of Catholicism on Italian post war reconstruction -- What's left? Religion and welfare policies in the 21st century in Italy and Germany -- Conclusion, 8.8.2024.
Includes bibliographical references and index
Keywords: Sozialstaat; Protestantismus; Katholizismus; Sozialpolitik; Geschichte; Deutschland; Italien; Welfare State -- Germany -- History; Welfare State -- Italy -- History; Public Welfare -- Religious aspects -- Christianity; Economics -- Religious aspects -- Christianity